Retracted: LncRNA‐LET relieves hypoxia‐induced injury in H9c2 cells through regulation of miR‐138. Issue 1 (21st June 2019) - Li, Yugeng; Li, Jianwei; Zhang, Pengzhen; Jiang, Xiaoying; Pan, Zhenrui; Zheng, Wenjian; Lin, Hongli
Abstract: Ischemic heart disease (IHD) is a common cardiovascular disease, occurs when coronary artery blood circularity cannot match with the heart's need. The present work attempted to study the effects of long noncoding RNA (lncRNA) low expression in tumor (LET) on the progression of IHD. H9c2 cells were injured by hypoxia to mimic a cell model of IHD. The effects of lncRNA‐LET on hypoxia‐injured H9c2 cells were tested by using cell counting kit‐8 assay, flow cytometry, and Western blot analysis. MicroRNA‐138 (miR‐138) expression was tested by a quantitative real‐time polymerase chain reaction, and the expression of c‐Jun N‐terminal kinase (JNK) and p38MAPK (p38–mitogen‐activated protein kinase) proteins was measured by Western blot analysis. We found that hypoxia exposure significantly repressed the viability of H9c2 cells, and induced apoptosis. Meanwhile, phosphorylation of JNK and p38MAPK was enhanced by hypoxia. The expression of lncRNA‐LET was repressed by hypoxia. Overexpression of lncRNA‐LET attenuated hypoxia‐induced injury in H9c2 cells. Moreover, miR‐138 was a downstream effector of lncRNA‐LET, that miR‐138 was highly expressed in lncRNA‐LET‐overexpressed cell. The cardioprotective effects of lncRNA‐LET were abolished when miR‐138 was silenced. In conclusion, this study revealed the cardioprotective function of lncRNA‐LET. lncRNA‐LET conferred its cardioprotective effects possibly via upregulation of miR‐138 and thus repressing the JNK and p38MAPK pathways. Abstract : In conclusion, this study revealed the cardioprotective function of long noncoding RNA (lncRNA)‐low expression in tumor (LET). lncRNA‐LET conferred its cardioprotective effects possibly via upregulation of microRNA‐138 and thus repressing the c‐Jun N‐terminal kinase and p38MAPK pathways. HIGHLIGHTS: 1. lncRNA‐LET is downregulated by hypoxia in H9c2 cells. 2. Overexpression of lncRNA‐LET protects H9c2 cells against hypoxia‐induced injury. 3. miR‐138 is positively regulated by lncRNA‐LET. 4. The cardioprotective effects of lncRNA‐LET are abolished by miR‐138 silence. 5. lncRNA‐LET represses the activation of the JNK and p38MAPK pathways via miR‐138.